Strategi Pelaksanaan Pendidikan PAI Berwawasan Multikultural di Sekolah - Ahmad Asrin (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2019)
This paper discusses how to build and develop Islamic Religious Education (PAI) subjects with multicultural insights in Schools, while the focus of the discussion is how to strategy in education with multicultural insights and how to develop them in Schools. The method used in this discussion is qualitative research library approach. The results of the discussion illustrate that the application of multicultural education in schools must be integrated with a variety of relevant subjects and are based on the social conditions of children and not merely the adoption of multicultural education concepts of other nations and the development of multicultural education design in schools consists of three stages, namely: analyzing factors potential multicultural nuances, determining approaches, methods and media for multicultural learning, and developing multicultural based learning designs. The conclusion of this research is that the forerunners of multicultural education must be integrated with a variety of relevant subjects with respect to plurality and heterogeneity. Keywords: Strategy of Implementation, PAI Subject, Multicultural Insights